Implementation of Youtube as a Learning Media Strengthening Cross-Cultural Understanding for BIPA Students - Ilmiah S, Himmatun; Muzdalifah, Muzdalifah (ppjbsip, 2022)
Culture shock is still a problem for foreign students and BIPA teachers, both during the learning process and outside of learning. This happens because there is no in-depth knowledge and adequate preparation related to cultural differences between countries so that misunderstandings often occur between students and between students and teachers. Therefore, strengthening Cross Cultural Understanding (CCU) learning is important to provide in-depth knowledge for BIPA teachers or students. This learning can be packaged very attractively using media that are in great demand by today's BIPA teachers and students. The purpose of this study is to describe the implementation of YouTube as a medium for strengthening CCU learning for BIPA students. Data collection was carried out through the distribution of a questionnaire instrument containing short questions to BIPA students. Instruments are created with the help of Google Forms.Â AbstrakGegar budaya masih menjadi sebuah problematika bagi pelajar asing maupun pengajar BIPA, baik saat proses pembelajaran berlangsung maupun saat di luar pembelajaran. Hal tersebut terjadi karena belum adanya pengetahuan mendalam dan persiapan yang cukup terkait perbedaan budaya antar negara sehingga sering kali terjadi kesalahpahaman antar pelajar maupun antar pelajar dengan pengajar. Oleh karena itu, penguatan pembelajaran Cross Cultural Understanding (CCU) penting untuk memberikan pengetahuan yang mendalam bagi pengajar ataupun pelajar BIPA. Pembelajaran tersebut dapat dikemas dengan sangat menarik menggunakan media yang banyak diminati oleh pengajar dan pelajar BIPA masa kini. Tujuan penelitian ini adalah mendeskripsikan implementasi YouTube sebagai media penguatan pembelajaran CCU bagi pelajar BIPA. Pengumpulan data dilakukan melalui penyebaran instrumen angket yang berisi pertanyaan singkat kepada pelajar BIPA. Instrumen dibuat dengan bantuan Google Form.